Novel nitrogen-doped reduced graphene oxide-bonded Sb nanoparticles for improved sodium storage performance. Issue 24 (1st June 2018) - Fang, Yuyan; Xu, Xin; Du, Yichen; Zhu, Xiaoshu; Zhou, Xiaosi; Bao, Jianchun
Abstract : Novel nitrogen-doped reduced graphene oxide-bonded Sb nanoparticles are developed using the ionic liquid Emim-dca as a nitrogen source for improved sodium storage performance. Abstract : As a promising anode material for sodium-ion batteries, Sb has attracted considerable attention due to its high theoretical capacity (660 mA h g −1 ). However, it exhibits poor cycling stability because of its great volume change during sodium ion uptake and release processes. In order to solve this problem, using the ionic liquid Emim-dca as a nitrogen source, novel nitrogen-doped reduced graphene oxide-bonded Sb nanoparticles (Sb/N-rGO) are produced by ball-milling and subsequent pyrolysis treatment. As an anode material for sodium-ion batteries, Sb/N-rGO shows high capacity, excellent cycling stability, and high rate performance. A high reversible capacity of 304.8 mA h g −1 is achieved even at a current density of 5 A g −1 . Even after 500 cycles, there is still 90.7% capacity retention (473.2 mA h g −1 ) at a current density of 0.1 A g −1 . The superior sodium storage performance can be attributed to strong bonding between Sb and pyrrolic nitrogen in nitrogen-doped reduced graphene oxide. The facile synthesis strategy can potentially be applied to other anode materials for sodium-ion batteries.